ResCA - 7th Semi-Annual Progress Report - The Nature Conservancy; AgroLAC (2020)
To advance the goals of the Resilient Central America (ResCA) program, we have achieved the following results in the October 2019 to March 2020 semester reporting period. Regarding climate change adaptation, this semester we trained a total of 711 people; 380 men (53.4%) and 331 women (46.6%). We also strengthened 36 institutions; 1 from the public sector at the national level; 5 from the public sector at subnational level and 30 local organizations. With collaborating institutions and stakeholders, 1 policy was proposed at the sub-national level. We achieved the adoption of 12 policies; 6 at the sub-national level, 5 at the national level and 1 at the regional/international level. We also achieved the implementation of 2 policies; 1 at the regional/international level and 1 at the national level.